Pengaruh Lingkungan Kewirausahaan, Risk Taking, dan Kreativitas (Studi Kasus Pada UMKM Sentra Kuliner Bratang Surabaya) - Muniroh, Hajar; Mulyati, Awin; Mulyati, Diana Juni (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
In recent years, Micro, Small, and Medium Enterprises (MSMEs) have demonstrated strong resilience amid Indonesia’s economic crises and have even managed to grow despite national economic pressures. This study aims to analyze the influence of entrepreneurial environment, risk-taking behavior, and creativity on the performance of MSMEs in the Bratang Culinary Center in Surabaya. The increasing number of business actors in the area serves as the basis for selecting this research object.This research uses a quantitative approach with a survey method, utilizing questionnaires distributed to MSME actors. The sample consists of all business units at the culinary center, totaling 55 enterprises. The data were statistically analyzed using multiple linear regression to determine both partial and simultaneous effects of the three independent variables on MSME performance. The results show that the entrepreneurial environment and risk-taking behavior each have a significant positive effect on MSME performance. Entrepreneurial policies, including licensing regulations, infrastructure support, and legal protection, are vital in supporting business activities. Risk-taking behavior also encourages MSME actors to make bold and strategic decisions, positively impacting their performance. However, the creativity variable yielded different results: although statistically significant, its influence on performance was negative. This suggests that creativity, if not directed appropriately or aligned with market preferences, can reduce business effectiveness. Simultaneously, the three variables have a significant effect on MSME performance, with the entrepreneurial environment and risk-taking behavior being the dominant factors. This study emphasizes the importance of a supportive external environment and the entrepreneur’s courage in decision-making as key drivers of MSME success.